010 Insights into hypertensive heart disease phenotypes: Spectrum of myocyte, interstitial and vascular changes by cardiovascular MRI. (5th May 2016) - Rodrigues, Jonathan CL; Amadu, Antonio Matteo; Dastidar, Amardeep Ghosh; Szantho, Gergley; Ratcliffe, Laura EK; Burchell, Amy E; Hart, Emma C; Hamilton, Mark CK; Nightingale, Angus K; Paton, Julian FR; Manghat, Nathan E; Bucciarelli-Ducci, Chiara
Abstract : Introduction: Hypertensive heart disease (HHD) can be classified into 4 left ventricular (LV) phenotypes: 1) normal, 2) concentric LV remodelling (LVr), 3) concentric LV hypertrophy (cLVH) and 4) eccentric LV hypertrophy (eLVH). The pathophysiology of the phenotypes is incompletely understood. We investigate extent of myocardial interstitial fibrosis and aortic impairment in HHD with cardiovascular magnetic resonance (CMR) Methods: 88 hypertensives (49 ± 14yrs, 57% male, SBP: 167 ± 30mmHg, DBP: 96 ± 14mmHg) underwent CMR (1.5T) and were compared with 29 age- and sex-matched normotensive controls (47 ± 14years, 59% male, SBP: 128 ± 12mmHg, DBP: 79 ± 10mmHg). Native T1 and extra-cellular volume fraction were measured. Circumferential myocardial strain was calculated by voxel-tracking. Aortic compliance was recorded. Results: At a structural level, increased LV mass in eccentric and concentric LVH resulted from: i) significantly increased myocardial cell volume (eLVH: 78 ± 19g/m 2 vs cLVH: 73 ± 15g/m 2 vs LVr: 55 ± 9g/m 2 respectively, P < 0.05) and ii) significantly increased interstitial volume (eLVH: 33 ± 10g/m 2 vs cLVH: 30 ± 10g/m 2 vs LVr: 19 ± 2g/m 2 respectively, P < 0.05). Functionally, eccentric and concentric LVH were associated with significantly impaired circumferential strain (eLVH: -12.8 ± 4.6% vs cLVH: -15.5 ± 3.1% vs LVr: -17.1 ± 3.2% vs controls: -17.4 ± 2.6% respectively, P < 0.05). Despite similar BP severity as LVH phenotypes, LV remodelling was associated with reduced aortic compliance but not associated with interstitial fibrosis or myocardial dysfunction relative to controls. Conclusion: Myocardial interstitial fibrosis is varies across HHD phenotypes with functional consequences. Eccentric LVH demonstrated the most interstitial fibrosis and systolic strain impairment. LV remodelling had normal myocardial, but abnormal aortic, function. Greater understanding of the pathophysiology of HHD phenotypes may help tailor future treatments.